Identification of Klebsiella pneumoniae and the Inhibitory Effect of Soursop Leaves (Annona muricata L.) on Swab Samples from Diabetes Patients - Dewi, Yulia Ratna; Ismawatie, Emma; Maulani, Yulita (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Diabetes mellitus is a chronic metabolic disorder that increases susceptibility to bacterial infections, particularly in chronic wounds. This study aims to identify Klebsiella pneumoniae in wound swab samples from diabetic patients and evaluate the antibacterial activity of soursop leaf (Annona muricata L.) extract. Wound swabs were collected aseptically and analyzed through Gram staining, biochemical testing, and selective media to confirm the presence of Klebsiella pneumoniae. The antibacterial effect of the extract was tested at concentrations of 20%, 40%, and 60% using the well diffusion method, with gentamicin and chloramphenicol as positive controls. Phytochemical screening revealed the presence of secondary metabolites such as alkaloids, flavonoids, tannins, saponins, and steroids. Results demonstrated a concentration-dependent inhibition of Klebsiella pneumoniae, with the highest inhibition zone observed at 60%, though smaller than the standard antibiotics. This study highlights the potential of Annona muricata extract as a natural antibacterial agent for diabetic wound infections and supports its role in developing alternative therapies. Further studies are recommended to optimize its efficacy and explore clinical applications.